(untitled) (Veterinary Science, 2026)
Leptospirosis is zoonotic bacterial disease with worldwide distribution, caused by spirochetes of the genus Leptospira. The incidence of the disease is higher in warm, humid climates, and seasonal outbreaks are frequent after floods. Domestic and wild animals act as reservoirs and shed leptospires in their urine, contaminating the environment. The association between contact with ambient water and the risk of Leptospira infection in temperate climates remains is not fully understood. The aim of this study was to determine the presence of pathogenic and non-pathogenic leptospires in environmental water samples from the northeastern region of La Pampa province through isolation by culture followed by genospecies identification using molecular biology techniques. Sampling was carried out after rainfall events, during the period September 2021–March 2025, during months with very low precipitation, 86 water samples from storm drains and wetlands were processed. Spirochetes were isolated from 10.5% (n=9) of the samples. None of the recovered strains carried the lipL32 gene, a well-established marker of pathogenic species. Partial sequencing of the 16S rRNA gene determined the following genomospecies: Leptospira ellinghausenii/Leptospira yanagawae/Leptospira meyeri (n=5), Leptospira idonii (n=2), Leptospira vanthielii (n=1), and Leptospira fainei (n=1). All isolates belonged to the saprophytic clade, except L. fainei, which is classified as belonging to the subclade P2 (intermediate group). The use of next-generation molecular approaches, together with serovar determination, is required for the accurate identification of spirochetes isolated from surface waters and for assessing their potential risk to human and animal health